Biologics and oral small‐molecule inhibitors for treatment of pediatric atopic dermatitis: Opportunities and challenges - Anqi Zhao; Chaolan Pan; Ming Li (Pediatric Investigation, 2023)
ABSTRACT Atopic dermatitis (AD) is a complex disease characterized by recurrent eczematous lesions and refractory pruritus that drastically impairs quality of life. Due to the chronic and relapsing course, patients are easily trapped in the debilitating condition. Classical therapies show limitations, especially for patients with moderate‐to‐severe phenotypes. Advanced new insights in targeted therapies exhibit great application prospects which were reinforced by the more profound understanding of the disease pathogenesis. However, the sustained efficiency, biosafety, and long‐term benefits still remain in further exploration. This review summarizes recent clinical studies on oral small‐molecule inhibitors and biological agents for pediatric AD patients, which provides the latest frontiers to clinicians.